(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Intraoperative common bile duct injury is a serious complication of hepatobiliary surgery and often requires definitive biliary reconstruction. Choledochoduodenostomy and Roux-en-Y hepaticojejunostomy are commonly used procedures, but their comparative postoperative outcomes remain clinically important. Aim & Objective: To compare the surgical outcomes of choledochoduodenostomy and Roux-en-Y hepaticojejunostomy in patients with intraoperative common bile duct injury, with respect to morbidity, recovery, biliary complications, and outcome. Materials & Methods: This prospective comparative study was conducted in the Department of General Surgery, S.N. Medical College, Agra, among 60 patients with intraoperative common bile duct injury. Patients were equally divided into Group A undergoing choledochoduodenostomy and Group B undergoing Roux-en-Y hepaticojejunostomy. Demographic profile, intraoperative details, ICU requirement, hospital stay, postoperative complications, biliary stricture, recurrent jaundice, readmission, mortality, satisfaction, and quality-of-life outcomes were recorded and compared. Results: Both groups were comparable for age and sex distribution. ICU requirement was significantly higher after choledochoduodenostomy than Roux-en-Y hepaticojejunostomy (6/30 vs 2/30; p=0.025). Mean hospital stay was longer in the choledochoduodenostomy group (8.80 ± 2.882 days) than the Roux-en-Y group (6.10 ± 1.882 days; p=0.016). Bile leak, wound infection, postoperative fever, pain burden, biliary stricture at 6 months (12/30 vs 5/30; p=0.015), readmission, and long-term recurrent jaundice (14/30 vs 3/30; p=0.039) were higher after choledochoduodenostomy. Final excellent outcome was more frequent after Roux-en-Y hepaticojejunostomy (18/30 vs 9/30; p=0.049). Conclusion: Roux-en-Y hepaticojejunostomy demonstrated better early recovery, fewer complications, lower stricture and recurrent jaundice rates, and superior outcome than choledochoduodenostomy, helping define the preferable reconstructive option in selected biliary injury patients.